SISTEM INFORMASI GEOGRAFIS LOKASI SEKOLAH TINGKAT SMA SEDERAJAT PADA KABUPATEN POHUWATO - Annahl Riadi (Teknosains, 2016)
This study aimed to obtain accurate data on the geographic informationto determine the location of high school in Pohuwato. This application uses the PHPprogramming language and implemented in real time. The method used in thisresearch is descriptive research method with the stages of research that startedfrom: the stage of the analysis, design, construction, testing, implementation,evaluation, and maintenance. System testing methods used are White Box Testingand Black Box Testing. At the White Box Testing method, based on research resultsand flowgraph created flowchart of the data obtained. Flowchart examined, ie thesite selection process. From the results of calculations using White Box Testingmethod, the value of the calculation result Cyclomatic Complexity = 5, Region = 5,and Independent Path = 5 who have met the eligibility requirements in terms ofsoftware. While the results of testing using the Black Box Testing method, the valueof measuring the level of ease, speed information, as well as the accuracy of thedata in order to meet the eligibility requirements in the application of the system.